Design goes to school: Opportunities to apply the design process in Chilean school education - Bravo, Úrsula; Cortés, Catalina; Rivera, Maritza; Ceric, Francisco; Lloyd, Peter; Jones, Derek (Base Diseño e Innovación, 2016)
The state of economic development of the country requires the formation of human capital that dominate higher-order thinking skills, as analytical thinking, creative problem solving and collaboration; all skills deployed extensively during the design process. At the school level, this is not resolved only with curricular changes, but requires teacher training and support.  There is empirical evidence of the international application of design thinking in the field of education among students and teachers. However, directly importing such models may not be effective given the cultural differences and particularities of the Chilean educational system. This project seeks to identify opportunities for the transfer of design thinking to chilean education, as well as develop and test a training program in conjunction with professors and directors of schools of various levels of dependency. An intervention was designed—in a training program mode—which was experienced by 20 teachers (four of them with managerial and/or administrative positions). A range of resources was used to collect, systematize and analyze the information (practical exercises, questionnaires, interviews, focus groups, arrays, etc.). In this article, we present the preliminary results of the project "Developing human capital for 21st century economies: Introducing design thinking to chilean schools", which has allowed us to identify problems in the field of curricula, school atmosphere and at the organizational level. These problems were addressed as opportunities by the teachers, applying tools delivered in the training.
Keywords: design thinking; design; education; teacher training; 21st century skills